Preoperative Risk Factors for Subsequent Ipsilateral ACL Revision Surgery After an ACL Restoration Procedure. Issue 1 (January 2023) - Sanborn, Ryan M.; Badger, Gary J.; Fleming, Braden C.; Kiapour, Ata M.; Fadale, Paul D.; Hulstyn, Michael J.; Owens, Brett D.; Proffen, Benedikt; Sant, Nicholas; Portilla, Gabriela; Freiberger, Christina; et al.
Background: Anterior cruciate ligament (ACL) revision surgery is challenging for both patients and surgeons. Understanding the risk factors for failure after bridge-enhanced ACL restoration (BEAR) may help with patient selection for ACL restoration versus ACL reconstruction. Purpose: To identify the preoperative risk factors for ACL revision surgery within the first 2 years after BEAR. Study Design: Case-control study; Level of evidence, 3. Methods: Data from the prospective BEAR I, II, and III trials were used to determine the preoperative risk factors for ACL revision surgery. All patients with a complete ACL tear (aged 13-47 years, depending on the trial), who met all other inclusion/exclusion criteria and underwent a primary BEAR procedure within 30 to 50 days from the injury (dependent on the trial), were included. Demographic data (age, sex, body mass index), baseline patient-reported outcomes (International Knee Documentation Committee [IKDC] subjective score, Marx activity score), preoperative imaging results (ACL stump length, notch size, tibial slope), and intraoperative findings (knee hyperextension, meniscal status) were evaluated to determine their contribution to the risk of ipsilateral ACL revision surgery. Results: A total of 123 patients, with a median age of 17.6 years (interquartile range, 16-23 years), including 67 (54%) female patients, met study criteria. Overall, 18 (15%) patients required ACL revision surgery in the first 2 years after the BEAR procedure. On bivariate analyses, younger age ( P = .011), having a contact injury at the time of the initial tear ( P = .048), and increased medial tibial slope (MTS; P = .029) were associated with a higher risk of ipsilateral revision surgery. Multivariable logistic regression analyses identified 2 independent predictors of revision: patient age and MTS. The odds of ipsilateral revision surgery were decreased by 32% for each 1-year increase in age (odds ratio, 0.684 [95% CI, 0.517-0.905]; P = .008) and increased by 28% for each 1° increase in MTS (odds ratio, 1.280 [95% CI, 1.024-1.601]; P = .030). Sex, baseline IKDC or Marx score, knee hyperextension, and meniscal status were not significant predictors of revision. Conclusion: Younger age and higher MTS were predictors of ipsilateral ACL revision surgery after the BEAR procedure. Younger patients with higher tibial slopes should be aware of the increased risk for revision surgery when deciding to undergo ACL restoration.